A Review of Building Window Glazing with High Performance in Heat Transfer - Sajede Karimian; Yousef Gorji Mehlabani (توسعه پایدار شهری)
Glazing is one of the important indicators of a building's energy efficiency, and extensive research has been done on it since the last decades. Poorly designed skylights, windows, and glazed surfaces can create an unpleasant environment. Currently, various types of glazing with different functions are used. The physical properties of glazing affect daylight quality, thermal properties, and energy-saving potential. This article examines the performance of various window glazing technologies and covers the physical characteristics of static glazing and dynamic glazing technologies. In window technologies. In this article, we discuss the relationship between the physical and optical parameters of different types of glazings and their heat transfer value. In addition, this article also provides readers with a wide range of information, including new research in glazing technologies. This review emphasizes this general relationship at the design stage so that designers have a broader view of product selection, as well as sufficient knowledge to ensure various other benefits for improved comfort, reduced mechanical loads, and improved energy performance. Among the main results, we found that, although several advances have been made in this field in the last decade, more research is needed to develop window technologies that not only have high insulating properties but can also generate energy.